Thermal performance of a concrete column as a sensible thermal energy storage medium and a heater. (October 2017) - Özrahat, Evrim; Ünalan, Sebahattin
Abstract: A square sectioned concrete column was constructed with its real dimensions in order to investigate the thermal performance of the concrete column which is proposed to be used as a heater and thermal energy storage medium in the building structure. For this purpose, a steel pipe was inserted in the lengthwise of the concrete column for air flow to store thermal energy from heated air to concrete column. Thermal performance of the column was investigated experimentally for various air flow temperatures and velocities as a function of operation time. Results of a week showed that concrete column can be used as a heater and also thermal energy storage medium in the building structure. In addition, it was shown that amount of heat released from concrete column can be controlled by air flow temperature, flow velocity and energy charging time. Investigated concrete column was also modeled three-dimensional by a CFD code and transient numerical results were validated by experimental results. The obtained high agreement with realizable k-epsilon turbulence model showed that CFD codes could be used for pre-calculations of the experiments and for numerical modeling of multi-story building with this novel heating system that is hard and expensive to study experimentally. Highlights: Concrete columns can be used as thermal energy storage medium and heater. Transient thermal performance of concrete column was investigated experimentally. Experimental results are attractive in terms of building heating. Concrete column was also modeled numerically. Numerical results obtained are compatible with experimental results.